Demethylation of Quinine Using Anhydrous Aluminium Trichloride - Aiyi Asnawi; As'ari Nawawi; Rahmana Emran Kartasasmita; Slamet Ibrahim (Journal of Mathematical and Fundamental Sciences, 2011)
Quinine is a natural alkaloid having a methoxy group bound to quinoline ring and an allyl group bound to quinuclidine ring. Demethylation of quinine applying strong acid such as HBr or HI at high temperature was unsuccessful. The aim of this research was to obtain demethylated quinine by means of mild and selective demethylation procedure to prevent the addition reaction of allyl group. Selective demethylation of quinine has been carried out using anhydrous aluminium trichloride as reagent. The demethylation product was achieved in 68.12% yield by mole ratio of quinine to anhydrous aluminium trichloride of 1 to 4 in dried methylene chloride under nitrogen atmosphere. The reaction was firstly carried out at 0°C for 4 h and after the reaction mixture reached room temperature, the reaction was continued up to 24 h.